2021
DOI: 10.1177/1847979021994509
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the socio-economic environment on the entrepreneurs behavior. Cases of cuba and ecuador

Abstract: Entrepreneurship is an important part of any economy today regardless of its level of development. However, not in all contexts do entrepreneurs operate in the same way, nor are they motivated by the same factors. This research seeks to identify possible coincidence factors and differences between entrepreneurs that operate in different contexts from the point of view of their historical evolution, the duration of these and the economic and social model applied in the countries. Specifically, a comparative stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 44 publications
1
1
0
2
Order By: Relevance
“…They showed that the qualities that characterise or distinguish entrepreneurs are similar even in different socio‐economic conditions. Furthermore, there were coincidences with previous studies on this subject (Perez‐Campdesuner et al, 2021).…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…They showed that the qualities that characterise or distinguish entrepreneurs are similar even in different socio‐economic conditions. Furthermore, there were coincidences with previous studies on this subject (Perez‐Campdesuner et al, 2021).…”
Section: Resultssupporting
confidence: 88%
“…The recent studies that assessed the relationship between entrepreneurship and economic activity at the national level were Furthermore, there were coincidences with previous studies on this subject (Perez-Campdesuner et al, 2021).…”
Section: Resultsmentioning
confidence: 71%
“…Según Pérez-Campdesuñer et al (2021), las cualidades que distinguen a los emprendedores depende de las variables que impulsan a los individuos a emprender, entre estas variables se destacan las siguientes: la edad, por ejemplo, en Cuba es en promedio varios años más tarde que en Ecuador; el inicio de la actividad emprendedora y el propósito de los usos de los ingresos. Esta última es diferente entre las dos poblaciones estudiadas; además, se evidencia que ambas evalúan emprendimientos relacionados con alimentos como de alto consumo, lo cual no es sorprendente ya que esta es una de las más altas prioridades necesidades básicas.…”
Section: Resultados Y Discusiónunclassified
“…Acorde con estos factores en un mapeo sistemático (Cajas et al, 2022) se recalcan en los resultados obtenidos en Latinoamérica a la perseverancia, la visión, la actitud del emprendedor y la cultura empresarial (Araya-| doi.org/10.33386/593dp.2024.2.2307 al., n.d.;Córdova et al, 2020;Hernández Herrera & Sánchez Rodríguez, 2017;Jordán et al, 2020;Loor Moreira et al, 2020;Pérez Quiroz & García Revelo, 2019;Pérez-Campdesuñer et al, 2021;Rivera et al, 2018;Sánchez Tovar et al, 2015;Valencia-Arias & Marulanda-Valencia, 2019). Adicionalmente se destaca que existen tres elementos básicos del espíritu empresarial como son las variables objetivas, conocimientos y habilidades para saber aplicarlas.…”
Section: Discussionunclassified